Development of Mathematics Learning Tools Based on Problem Posing Learning Models to Improve Mathematical Communication Ability and Learning Independence of Junior High School Students - Fitriyanti Fadilla; Sahat Saragih; KMS. M. Amin Fauzi (BIRCU, 2021)
This study aims to produce a valid, practical, and effective problem posing learning model-based learning tool for Class VIII students of SMP Nusantara Lubuk Pakam, to analyze the improvement of students' mathematical communication skills taught with learning tools developed based on the Problem Posing Learning model in SMP. Nusantara Lubuk Pakam, to analyze the achievement of student learning independence taught with learning tools developed based on the Problem Posing Learning model at SMP Nusantara Lubuk Pakam, as well as to analyze the answer process of SMP Nusantara Lubuk Pakam students in solving test questions of mathematical mathematical communication skills. The data were obtained through the validation sheet of teaching materials, observation sheets, student response questionnaires, mathematical communication skills test instruments and student learning independence questionnaires. This study uses the 4-D development model Thiagarajan, Semmel and Semmel by developing teaching materials with problem posing learning. Based on the validation results of the value of learning tools developed through the Problem Posing learning model, the validator team met the valid and practical criteria. The implementation of the learning tools developed through the Problem Posing learning model was in good criteria, namely 87.78% in trial II. Classical mastery of student learning has been achieved in the second trial by 90%. The achievement of learning objectives has been achieved in the second trial, which is 83.39%. Student responses to components and learning activities 94.11% have shown a positive response to the components of learning tools and learning activities developed.